PERTUMBUHAN EKONOMI DAN PENDAPATAN ASLI DAERAH PROVINSI KALIMANTAN BARAT MELALUI PENDEKATAN KAUSALITAS GRANGER - Suharlina, Helly; Dwiastuti, Ninuk; Saputra, Rendy Amy; Suradi, Romi (Business, Economics dan Entrepreneurship, 2024)
One of the successes in developing a region can be seen from level of economic growth, for this reason each region always makes efforts either by optimizing the level of economic growth in order to move the region in order to lead to a better life. The aim of this research is to test and analyze the influence of Original Regional Income (PKM) on Economic Growth and to test and analyze the causal relationship between Original Regional Income (PAD) on the Economic Growth of Districts/Cities in West Kalimantan Province. The data used is secondary data, the analysis tools used are Linear Regression and the Grager Causality test. The research results show that Original Regional Income (PAD) has a positive and significant effect on Economic Growth in West Kalimantan Province and there is no causal relationship between Original Regional Income (PAD) and Economic Growth, there is only a unidirectional relationship between Original Regional Income (PAD) with Economic Growth and does not happen vice versa.